Theoretical and experimental study of the vibrational spectra of 1.5-dimethylcytosine - Brandán, S.A. (2008)
The Raman spectra of the solid 1,5-dimethylcytosine and the FTIR spectra at room and low temperatures respectively have been registered. Quantum mechanical calculations of energies, geometries and vibrational wavenumbers were carried out by using ab initio (HF) and Density Functional Theory (DFT/BLYP and B3LYP) methods with different basis sets. The best level of theory in order to reproduce the experimental wavenumbers is the BLYP method with the 6-31G* basis set. The theoretical calculations indicate the presence of four stable tautomers of 1,5-dimethylcytosine: amino-oxo; imino-oxo (a and b) and imino-hidroxy. Their geometries were optimised by using the BLYP/6-31G* method, being the amino-oxo tautomer the most stable, followed by the imino-oxo tautomer, while the imino-hidroxy one is the most unstable. The complete assignment of the observed bands in the vibrational spectra of the amino-oxo tautomer is proposed in this work. © 2007 Elsevier B.V. All rights reserved.